1994
DOI: 10.1111/j.1600-0773.1994.tb01085.x
|View full text |Cite
|
Sign up to set email alerts
|

Function of the Auditory and Visual Systems, and of Peripheral Nerve, in Rats after Long‐Term Combined Exposure to n‐Hexane and Methylated Benzene Derivatives. I. Toluene

Abstract: Rats were exposed to n-hexane, toluene, or toluene together with n-hexane, each solvent 1000 p.p.m. (1000 + 1000 p.p.m. in combined exposure), 21 hr/day, 7 days/week during 28 days. Neurophysiological recordings were made 2 days, 3 months, and one year after end of exposure. A reduction in auditory sensitivity, recorded by click evoked auditory brainstem response, was observed 2 days after exposure to toluene alone, or to toluene together with n-hexane, but not after exposure to n-hexane alone. The reduction l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 35 publications
1
8
0
2
Order By: Relevance
“…Our analysis provided evidence that when the number of solvents exceeded 5, the risk estimate was 4.22 times higher. Several animal studies have confirmed that exposure to combinations of some solvents (mixtures of solvents) will contribute to greater hearing loss than it was found in single-solvent exposures [49][50][51][52][53]. The human studies have also confirmed such results [35].…”
Section: Ijomeh 2017;30(4)supporting
confidence: 68%
“…Our analysis provided evidence that when the number of solvents exceeded 5, the risk estimate was 4.22 times higher. Several animal studies have confirmed that exposure to combinations of some solvents (mixtures of solvents) will contribute to greater hearing loss than it was found in single-solvent exposures [49][50][51][52][53]. The human studies have also confirmed such results [35].…”
Section: Ijomeh 2017;30(4)supporting
confidence: 68%
“…For the solvents investigated in our study, there is evidence available on the ototoxicity of high concentrations of toluene, both alone or as a component of solvent mixtures (1,2,7,15,31). Animal experiments which evaluated the effects of combined exposures to toluene and ethanol (2 of the solvents used in the studied company), revealed that exclusive exposure to ethanol did not affect the auditory system (32,33).…”
Section: Acoustic Reflex Measurementsmentioning
confidence: 99%
“…Loss of hair cells in the cochlea was found to result from the toluene exposure a, Nylen et al 1994, Pryor et al 1983. The symptoms of the serotonin syndrome are changed (CastillaSerna et al 1993) and changes in the circadian susceptibility are suggested (Harabuchi et al 1993).…”
Section: Subchronic and Chronic Inhalation Toxicitymentioning
confidence: 99%